Effects of considering preferential diffusion and flame stretch in FGM method for numerical simulations of hydrogen/air flames - Kazuhiro KINUTA; Reo KAI; Ryoichi KUROSE (Journal of Thermal Science and Technology, 2024)
One-dimensional numerical simulations of an unstretched propagating hydrogen/air premixed flame and two-dimensional numerical simulations of outwardly propagating hydrogen/air laminar premixed flames are performed using a flamelet-generated manifold (FGM) method. The effects of considering preferential diffusion and flame stretch in the FGM method are investigated in detail. The results of the one-dimensional numerical simulations show that the flame behavior can be qualitatively reproduced without considering both these two phenomena, but it can be predicted more precisely by considering preferential diffusion. On the other hand, the results of the two-dimensional numerical simulations show that considering both these two phenomena is essential to accurately predict the behavior of stretched hydrogen/air premixed flames at an equivalence ratio of less or more than 0.7. The results also show that the consideration of preferential diffusion and flame stretch is less important at an equivalence ratio of around 0.7. In addition, the validity of an assumption that the Lewis numbers of each species are constant, which is used in most previous studies, is investigated. The results show that assuming constant Lewis numbers worsens the prediction accuracy. The computational cost of the FGM method considering both preferential diffusion and flame stretch is about 1/15 that of the detailed calculation for the two-dimensional numerical simulations, which indicates the efficiency of the extended FGM method.